Immunoperoxidase labelled antibody staining in differential diagnosis of central nervous system haemangioblastomas and central nervous system metastases of renal carcinomas. Issue 8 (August 1986) - Andrew, S M; Gradwell, E
Abstract : The problem of the differential diagnosis both of central nervous system haemangioblastomas and metastases of renal clear cell carcinomas was investigated by immunoperoxidase labelled antibody staining of five cases each of haemangioblastoma and metastatic renal carcinoma. Staining using anticarcinoembryonic antigen (CEA), antikeratin, antifactor VIII related antigen, and antibrush border was unhelpful. All five of the haemangioblastomas were negative and all five of the metastases were positive for epithelial membrane antigen (EMA), as defined by immunoperoxidase staining. This shows that commercially available anti-EMA monoclonal antibody is useful in distinguishing the two pathological entities.